Preliminary Study of Nitration of PETRONAS Calcined Cokes For Water Dispersible Solid Fuel - Hidayah Binti Awalludin, Hidayah (Universiti Teknologi Petronas, 2009)
The objectives of this work are to determine if the calcined coke can be water dispersible, to study the improvements of calcined coke after treating with nitration, and to compare the characteristics of solid fuel and nitrated calcined coke to see if there is a possibility for the coke to be developed to water dispersible solid fuel. Currently calcined coke primary use is in making carbon anodes for aluminum industry. Because of the insoluble properties, the usage of calcined coke is limited. Plus, calcined coke has low volatile matter, high ash content and high fixed carbon content which make it unsuitable for solid fuel. Since nitration can remove ash content and increase solubility of a compound, by having this project we can see how the properties of calcined coke can be improved after being treated with nitration process. The keywords for this project are calcined coke, nitration, solid fuel, volatile matter, ash content, fixed carbon content and solubility.